2021
DOI: 10.1038/s41598-021-88250-3
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure and choroidal thickness postural changes in multiple system atrophy and Parkinson’s disease

Abstract: To evaluate intraocular pressure (IOP) and choroidal thickness (ChT) postural changes in multiple system atrophy (MSA), Parkinson’s disease (PD) patients and healthy controls (HC). 20 MSA patients, 21 PD patients and 14 HC, were examined. All subjects underwent a complete examination, including corneal thickness, ChT, IOP and axial length (AL) measurements. IOP measurement was performed in supine, sitting, and standing positions, whereas ChT in sitting and standing positions. Supine to standing IOP variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
(5 reference statements)
0
21
1
Order By: Relevance
“…17 De Bernardo et al demonstrated how both healthy subjects and patients with MSA or PD showed IOP increase in supine position, this increase was higher in patients with MSA. 17 In addition, an IOP increase in obese patients in the supine positions compared to the sitting and the standing was rstly reported in 2015 by Geloneck et al in which, similarly to the present study, authors measured the IOP of obese patients in 3 different positions. 18 The results of the present study not only con rm that ΔIOPs between supine and other positions were statistically signi cant (P < 0.05) in both overweight subject and normal weight controls but, in addition to previous studies, they show that ΔIOP in supine and 5'standing positions was higher in overweight subject than in normal weight controls (P < 0.05).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…17 De Bernardo et al demonstrated how both healthy subjects and patients with MSA or PD showed IOP increase in supine position, this increase was higher in patients with MSA. 17 In addition, an IOP increase in obese patients in the supine positions compared to the sitting and the standing was rstly reported in 2015 by Geloneck et al in which, similarly to the present study, authors measured the IOP of obese patients in 3 different positions. 18 The results of the present study not only con rm that ΔIOPs between supine and other positions were statistically signi cant (P < 0.05) in both overweight subject and normal weight controls but, in addition to previous studies, they show that ΔIOP in supine and 5'standing positions was higher in overweight subject than in normal weight controls (P < 0.05).…”
Section: Discussionmentioning
confidence: 96%
“…16 An IOP increase in supine position was also reported in patients affected by multiple system atrophy (MSA) and Parkinson's disease (PD). 17 De Bernardo et al demonstrated how both healthy subjects and patients with MSA or PD showed IOP increase in supine position, this increase was higher in patients with MSA. 17 In addition, an IOP increase in obese patients in the supine positions compared to the sitting and the standing was rstly reported in 2015 by Geloneck et al in which, similarly to the present study, authors measured the IOP of obese patients in 3 different positions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…But more importantly, our PSP and healthy controls showed comparable axial length, ensuring the reliability of retinal layers comparisons between groups. As a matter of fact, evidence demonstrates that axial length may influence the measurement of retinal and choroidal thickness [ 21 , 22 ], and none of the previously published studies on this topic compared patients and controls according to these parameters. Finally, all our patients and healthy controls were Caucasian.…”
Section: Discussionmentioning
confidence: 99%
“…It should be subject to systemic vascular monitoring, that could also explain the slight decrease when going from the supine to the standing position, that conversely becomes an increase 5 min after maintaining the standing position. [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%